Beyond 'plata o plomo': drugs and state reconfiguration in Colombia - Duncan, Gustavo (Cambridge elements : elements in politics and society in Latin America, 2022)
This Element introduces the concept of oligopoly of coercion to interpretate the interaction between drug trafficking and reconfiguration of the state in Colombia. Three elements are central to this interpretation: corruption in oligopolies of coercion must be understood as a payment by drug traffickers for acting like a parallel state; the state criminalizes more drug as merchandise than drug as capital – its equivalent in money; the politics and war around drug trafficking in Colombia should be understood as the way in which peripheral societies access global markets through the ruling institutions of private armies. With these elements, the author focuses on the dynamics of the reconfiguration of the state in Colombia after the cocaine boom in the mid-70s and the evolution of the private armies in Colombia.